Mobile security and privacy in smartphone technology - Ibrahim, Mohamed; Supayah, Ganesin; Ibrahim, Jamaludin (International Journal of Computer Science and Information Technology Research, 2015)
Such is the case with mobile technology, particularly smartphones, which have exploded in popularity in recent years. According to market analysis firm ABI Research, 370 million smartphones were in use globally last year. Mobile devices face an array of threats that take advantage of numerous vulnerabilities commonly found in such devices. These vulnerabilities can be the result of inadequate technical controls, but they can also result from the poor security practices of consumers. Many researchers and practitioners are expecting a major security incident with mobile phones ever since these devices began to become more powerful: with increased processing power and memory, increased data transmission capabilities of the mobile phone networks, and with open and third-party extensible operating systems, phones become an interesting target for attackers. However, in this paper we highlighted mobile phone security and recommendation for mobile security.